Analysis of the Fracture Mechanism of Ti-6Al-4V Alloy Rods That Failed Clinically After Spinal Instrumentation Surgery. Issue 13 (1st July 2015) - Yamanaka, Kenta; Mori, Manami; Yamazaki, Ken; Kumagai, Ruriko; Doita, Minoru; Chiba, Akihiko
<x xml:space="preserve">Abstract</x> Study Design. Retrieval analysis of 2 Ti-6Al-4V alloy rods that fractured after spinal instrumentation surgery. Objective. To determine the mechanism that underlies fractures of Ti-6Al-4V alloy rods after spinal instrumentation surgery from a materials science viewpoint. Summary of Background Data. Rod failures after spinal instrumentation surgery are often reported and many case-based studies have been published. However, the details of the mechanism that underlies the fractures have not yet been fully elucidated. Methods. Two patients, a 71-year-old female and an 11-year-old male, underwent radiography and removal of their fractured rods. The latter patient had been treated using the growing-rod method. Metallurgical failure analysis of the retrieved rods was conducted, and material properties were compared between the unused and fractured rods. Results. The microstructures and mechanical properties of the Ti-6Al-4V alloy rods that failed after spinal instrumentation surgery were similar to those of unused rods. Analysis of the fracture surfaces clearly identified fatigue cracking in both cases that would have lowered the resistance of the rods to failures caused by external stresses. Shot blasting the surfaces of Ti-6Al-4V alloy rods and bending the rods to fit particular contours, which is always conducted during spinal instrumentation surgery, probably introduced fatigue cracking because the alloy is highly notch sensitive. Conclusion. Improvements should be made to rod design and/or rod material, because the fatigue resistance of titanium alloys is intrinsically lower than that of other commercially available rod materials, including cobalt-chromium alloys. These imperfections may have greater consequences for the growing-rod method and pseudarthrosis, where the rods are not completely fixed, and they subsequently suffer from severe long-arm moments. Level of Evidence: N/A